An Empirical Study on Trade Openness and Economic Growth : The Malaysian Experience 1970-2002 - Chen, Jen Eem (2004)

(untitled)
This paper examine the effects of trade openness on Malaysia's economic growth. This study is based on anually time series for year 1970-2002. In doing this study, a general production function is employed and is expanded by adding trade openness indicators. Two groups of openess measures are used. The first group is the volumes of trade while the second is the trade restriction. The estimated result show that volumes of trade is positively and significantly associated with growth while trade barrier has inverse relationship with growth. The findings are generally in line with the literature and previous empirical studies, with the view that openness of trade is favorable in promoting economic growth.